Don’t Go Viral: An Evidence-Based Practice Project for Increasing Seasonal Influenza Vaccine Rates on a College Campus - Wasco, Jennifer J. (Building Healthy Academic Communities Journal, 2017)
Aim: To describe the effectiveness of an evidence-based practice (EBP) project on a college campus using an educational campaign that leveraged technology as well as traditional marketing strategies for the dissemination of valuable, reliable health information about the seasonal influenza virus and seasonal influenza vaccination. Background: Despite the typical seasonal influenza vaccine effectiveness (VE) of approximately 50% - 60% (Centers for Disease Contol and Prevention, 2016c), some groups of individuals, such as young adults, do not take advantage of obtaining the immunization for a variety of reasons. Methods: Students (N=55) at a small private university in southwestern Pennsylvania agreed to participate in an EBP project between September 2015 and October 2015. Project participants were sent a link to an animated online video about seasonal influenza, and an optional text message reminder was sent to encourage vaccination against the virus. An electronic survey was utilized to identify demographics and confirm the effectiveness of the campaign methods. Results: Due to the limited number of survey responses, a broad scale conclusion of intervention effectiveness cannot be applied against the larger college student population nationally. However, the results from the participants who viewed the online educational video showed a favorable reaction to this type of intervention. Conclusions: Based on the EBP project results, when developing health-related material and programming, consideration needs to be given to the college student population’s preferences on learning. Given the computer usage statistics of the college-age population and the results of this project, the matching of the video to the population’s preferred medium is supported.